Acute severe hypertension associated with acute gastroenteritis in children. Issue 11 (15th September 2020) - Fishbein, Jennifer E.; Sethna, Christine B.; Singer, Pamela; Castellanos‐Reyes, Laura
Abstract: Acute severe hypertension in otherwise healthy children with acute illness requiring hospitalization for BP management is uncommon and warrants immediate evaluation. We describe 10 cases of children presenting with acute gastroenteritis and found to have acute severe hypertension. They required admission to the hospital for antihypertensive treatment, including 2 to the intensive care unit, but all had normalization of BP and were able to stop treatment with resolution of the acute illness. All patients had thorough testing for secondary causes of hypertension and for signs of end‐target organ damage, which were unremarkable. To our knowledge, acute severe hypertension in the setting of acute gastroenteritis without underlying kidney pathology and with complete resolution after illness has not been previously described. The mechanism of this association is not clear, although activation of the sympathetic nervous system is suspected. These cases illustrate the importance of thoroughly assessing BP in the acute setting.